Relationship between changes in the business environment, innovation strategy selection and firm's performance: Empirical evidence from Slovenia - Dušan Gošnik; Klemen Kavčič; Maja Meško; Franko Milost (Administrative Sciences, 2023)
This article studies the relationship between changes in the external business environment, a firm's innovation strategies towards customers, and performance. A model of relations was developed, as well as a hypothesis: "The use of the differentiation strategy has a positive effect on firm's performance. SMEs that use the differentiation strategy achieve better performance than those who use one of the other strategies (low-cost strategy, focus strategy, or an overtaking strategy)". The empirical study includes a population of 3007 SMEs and a sample of 163 SMEs. The firm's performance was measured using financial measures such as return on equity (ROE) and return on assets (ROA), operational measures such as economic value added (EVA) and comprehensive measures such as credit rating (CR). The structural equation modelling (SEM) approach was used for data analysis. Based on the results, we can confirm that changes in a firm's external environment affect the firm's strategy towards customers, which influences the performance of a firm. The empirical study confirmed that firms using the differentiation strategy indicate higher performances (ROA, EVA, and CR) than those using any other strategy. Results also show that high-performance SMEs incorporate customer perspectives into strategy selection. The most significant influence on the firm's selection of the differentiation strategy was found in cases when the firm cooperates with new customers with whom it has not collaborated thus far. SMEs that use a low-cost strategy, focus strategy, or overtaking strategy are less successful than companies that use a differentiation strategy. The developed model of relations in this research has special meaning for researchers and managers in the field of strategic management, strategy selection and implementation, as well as performance of SMEs.
Keywords: 350; changes; customer; differentiation; innovations; performance; SMEs; strategic management; strategy